Flame-retardant wear-resistant low-smoke halogen-free material and preparation method thereof
By preparing flame retardant capsules cross-linking with modified polyacrylate segments and forming a complex spatial mesh structure through flame retardant curing agent, the shortcomings of polyacrylate materials in flame retardant and wear resistance are solved, and the overall performance of the material is significantly improved.
Patent Information
- Application Number
- CN202411787180.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polyacrylate materials have shortcomings in flame retardant and wear resistance, and it is difficult to meet the application needs of high-temperature and high-risk environments.
The flame retardant capsules are prepared to form a support by crosslinking with the modified polyacrylate segments, and further crosslinking with the polyacrylate segments through the flame retardant curing agent to form a complex spatial network structure, which jointly improves the flame retardant and wear resistance of the material.
The flame retardant and wear resistance of the material are significantly improved. Through the synergistic action of the flame retardant capsule and the flame retardant curing agent, an effective flame retardant layer and wear resistance structure are formed, which enhances the overall performance of the material.
Smart Images

Figure BDA0005174350690000031 
Figure BDA0005174350690000061 
Figure BDA0005174350690000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyacrylate processing, and in particular to a flame-retardant, wear-resistant, low-smoke, halogen-free material and a preparation method thereof. Background Art
[0002] The research and development of flame-retardant and wear-resistant polyacrylate materials has gone through several stages, mainly focusing on improving the flame retardancy and wear resistance of the materials to meet the needs of different industrial fields. The initial polyacrylate materials have attracted widespread attention due to their excellent processing performance, heat resistance and chemical stability. However, traditional polyacrylate materials are weak in flame retardancy, which limits their application in high temperature and high-risk environments. In order to improve this shortcoming, flame retardants were added to polyacrylates. Halogen-containing flame retardants were initially used. Although effective, due to environmental problems with halogens, they have gradually been replaced by more environmentally friendly halogen-free flame retardants, such as aluminum hydroxide, phosphorus-based flame retardants, etc. At the same time, in order to improve the wear resistance of the material, researchers have enhanced the mechanical strength and surface hardness of polyacrylates through cross-linking, filling with nanoparticles and other methods.
[0003] Prior art CN110066478A discloses a flame-retardant, low-smoke, wear-resistant PVC floor and a preparation method thereof, comprising the following substances in parts by weight: 80-100 parts of PVC5 type resin, 35-45 parts of plasticizer, 20-35 parts of calcium silicate crystal fiber, 35-50 parts of white carbon black, 150-200 parts of melamine cyanurate, 5-10 parts of stabilizer, 3-6 parts of lubricant, 15-20 parts of epoxy soybean oil, 4-6 parts of anti-aging agent and 0-2 parts of colorant. Melamine cyanurate is added to reduce the smoke generated when PVC is burned, thereby playing a role of flame retardancy and smoke reduction. White carbon black is added to improve the wear resistance of PVC, thereby changing the defect that aluminum hydroxide and magnesium hydroxide are added as flame retardants to negatively affect physical properties.
[0004] However, the above patent content is to add auxiliary materials inside the resin to improve the flame retardant and wear resistance of the material. However, the calcium silicate crystal fiber in the auxiliary material will play a guiding role for the burning molten resin due to its fiber structure during the combustion of the material, causing the combustion products to spread and the flame to spread, thereby making the flame retardant performance of the material need to be further improved. In addition, the polarity of inorganic auxiliary materials such as calcium silicate crystal fiber and white carbon black is quite different from that of the resin, which may easily lead to weak interfacial bonding of the material, so that the wear resistance of the material needs to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The object of the present invention is to provide a flame retardant, wear-resistant, low-smoke, halogen-free material and a preparation method thereof, so as to solve the technical problem in the prior art that the flame retardant and wear-resistant properties of polyacrylate need to be further improved.
[0007] The purpose of the present invention can be achieved by the following technical solution: A method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material comprises the following steps:
[0008] S1. Add self-repairing capsules, vinyl triethoxysilane, sodium hydroxide and deionized water into a reactor, raise the temperature of the reactor to 30-50°C, keep the temperature for 3-5h, and post-treat to obtain flame-retardant capsules;
[0009] The reaction principle for preparing flame-retardant capsules is as follows: under the catalysis of alkaline conditions, the siloxane on the vinyltriethoxysilane is hydrolyzed to form a silanol structure and reacts with the hydroxyl groups on the surface of the self-repairing capsules, so that a large number of double bonds are cross-linked on the surface of the self-repairing capsules, and finally flame-retardant capsules are prepared.
[0010] S2, adding modified polyacrylate and dimethyl sulfoxide into a reactor, raising the temperature of the reactor to 150-160°C, stirring for 15-20 minutes, adding azobisisobutyronitrile and flame retardant capsules into the reactor, and reacting for 20-30 minutes to obtain flame retardant polyacrylate;
[0011] The reaction principle for preparing flame-retardant polyacrylate is as follows: under high-temperature melting and the catalysis of azobisisobutyronitrile, the double bonds on the surface of modified polyacrylate segments and flame-retardant capsules are activated to generate free radicals, which are then continuously cross-linked to form a polymer system supported by flame-retardant capsules, and finally flame-retardant polyacrylate is prepared.
[0012] S3, adding flame retardant polyacrylate, diisopropyltin methoxy compound and dimethyl sulfoxide into a reactor, introducing nitrogen protection, raising the temperature of the reactor to 70-80°C, keeping the temperature for reaction for 20-30 minutes, adding a flame retardant curing agent into the reactor, keeping the temperature for reaction for 1-2 hours, and post-treating to obtain cured polyacrylate;
[0013] The reaction equation for preparing cured polyacrylate is:
[0014]
[0015] Where:
[0016] The reaction principle for preparing the cured polyacrylate is as follows: under the catalysis of the removing agent diisopropyltin methoxy compound and high temperature, methanol is removed from the polymer chain segment, and under the protection of nitrogen, the exposed isocyanate group on the flame retardant polyacrylate reacts with the epoxy group on the flame retardant curing agent to form a five-membered oxazolidinone ring structure, and finally the cured polyacrylate is prepared.
[0017] S4, adding the solidified polyacrylate, the flame retardant capsule and the auxiliary materials into a twin-screw extruder for melt extrusion to obtain a flame retardant and wear resistant material.
[0018] Furthermore, in step S1, the amount ratio of self-repairing capsules, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water is 8-10g:2-3g:0.8-1g:30-50mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a flame-retardant capsule; in step S2, the amount ratio of modified polyacrylate, dimethyl sulfoxide, azobisisobutyronitrile and flame-retardant capsule is 8-10g:30-40mL:0.8-1g:2-3g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 120-150°C, and reduced pressure distillation is performed until no liquid is extracted to obtain a flame-retardant polyacrylate.
[0019] Furthermore, in step S3, the amount ratio of flame retardant polyacrylate, diisopropyltin methoxy compound, dimethyl sulfoxide and flame retardant curing agent is 8-10g:3-5g:30-40mL:2-3g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 120-150°C, and the reduced pressure distillation is carried out until no liquid is extracted to obtain solidified polyacrylate; in step S4, the amount ratio of solidified polyacrylate, flame retardant capsule and auxiliary material is 80-100g:10-15g:20-40g, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 170°C, 185, 185°C, 200°C, 200°C, 210°C, 210°C, the main engine speed of the twin-screw extruder is 100-120rpm, and the pressure is 80-120bar.
[0020] Further, in step S4, the auxiliary materials include: a plasticizer, a stabilizer, a lubricant and an antioxidant, and the amount ratio of the plasticizer, the stabilizer, the lubricant and the antioxidant is 15-25g:3-5g:1-5g:1-5g, the plasticizer is one or more of dioctyl phthalate, diisononyl phthalate and tributyl citrate; the stabilizer is one or two of butylated hydroxytoluene and triphenyl phosphite; the lubricant is one or more of calcium stearate, oxidized polyethylene wax and montan wax; the antioxidant is one or more of tri-tert-butyl hydroxyphenyl acrylate, tetramethyl dihydroxyphenyl acrylate and tri-tert-butyl hydroxyphenyl acrylate.
[0021] Furthermore, the preparation method of the self-repairing capsule comprises the following steps:
[0022] A1. Add 3-(methacryloyloxy)propyltrimethoxysilane, tetramethyltetravinylcyclotetrasiloxane, barium peroxide, benzophenone and aluminum isopropanol into a reaction kettle and stir for 5-10 minutes to obtain a modified oil;
[0023] A2, adding the modified oil phase solution into a high-speed homogenizer, and pouring the aqueous phase into the modified oil liquid, setting the speed of the high-speed homogenizer to 8000-9000rpm, stirring at room temperature for 20-30min, to obtain a modified emulsion;
[0024] A3. Add the modified emulsion into the reactor and stir. Add 1-2 mol / L hydrochloric acid solution into the reactor to adjust the pH value of the system to 4-5. Raise the temperature of the reactor to 40-50°C. After keeping the temperature for 3-4 hours, add aluminum isopropanol into the reactor. After keeping the temperature for 3-4 hours, add aluminum isopropanol again. Keep the temperature for 8-12 hours. After post-treatment, obtain the self-repairing capsule.
[0025] The reaction principle for preparing self-healing capsules is as follows: after pouring the modified liquid into the modified oil and stirring at high speed, the reaction system produces a water-in-oil structure. After adjusting the pH of the system, the aluminum isopropanol in the oil phase solution is hydrolyzed at the interface between the water and oil phases and finally hydrolyzed on the surface of the oil phase droplets to produce a stable cross-linked structure. After adding aluminum isopropanol, a stable dense structure is further formed on the capsule surface, and finally self-healing capsules are prepared.
[0026] Further, in step A1, the stirring rate of the reactor is 80-120rpm, and the amount ratio of 3-(methacryloyloxy)propyltrimethoxysilane, tetramethyltetravinylcyclotetrasiloxane, barium peroxide, benzophenone and aluminum isopropanol is 3-5g:5-8g:0.3-0.5g:0.3-0.5g:20-30mL; in step A2, the amount ratio of modified oil and modified liquid is 2-3g:10-15mL, and the modified liquid is prepared by polyvinyl alcohol and deionized water at a ratio of 1-2g:30-40mL; step In step A3, the dosage ratio of the modified emulsion and aluminum isopropanol is 40mL:3.6-5.4mL, and the dosage ratio of the aluminum isopropanol added twice is 0.8-1:1. The post-treatment includes: after the reaction is completed, after the temperature of the reaction liquid is lowered to room temperature, the mixed liquid is centrifuged using a centrifuge, and the speed of the centrifuge is controlled to be 3000-5000rpm. After centrifugation for 10-15min, the precipitate is collected, and after washing with anhydrous ethanol and deionized water for 3-5 times, the precipitate is placed in a drying oven at a temperature of 60°C and vacuum dried until the precipitate is constant weight to obtain a self-healing capsule.
[0027] Furthermore, the preparation method of the modified polyacrylate is as follows: dimethylaminoethyl acrylate, 1,2-isopropylidene glycerol 2-cyanoacrylate, azobisisobutyronitrile and N,N-dimethylformamide are added to a reactor and stirred, and after nitrogen protection is introduced, methacryloyl isocyanate solution is added dropwise to the reactor, the temperature of the reactor is increased to 70-80°C, and the reaction is kept warm for 2-4 hours, and then the temperature of the reactor is reduced to 40-50°C, and the protective liquid is continued to be added dropwise to the reactor, and the reaction is kept warm for 20-40 minutes, and the modified polyacrylate is obtained by post-treatment.
[0028] The reaction equation for preparing modified polyacrylate is:
[0029]
[0030] Where:
[0031] The reaction principle for preparing modified polyacrylate is as follows: under the protection of nitrogen, the isocyanate group remains stable in the process of free radical polymerization of dimethylaminoethyl acrylate, 1,2-isopropylidene glycerol 2-cyanoacrylate and methacryloyl isocyanate, and the isocyanate group reacts with ethanol under alkaline conditions to protect the isocyanate group, and finally the modified polyacrylate is obtained.
[0032] Furthermore, the dosage ratio of dimethylaminoethyl acrylate, 1,2-isopropylidene glycerol 2-cyanoacrylate, azobisisobutyronitrile, N,N-dimethylformamide, methacryloyl isocyanate solution and protective liquid is 6-8g:8-10g:1-2g:60-80mL:20-30mL:10-20mL, the methacryloyl isocyanate solution is prepared by methacryloyl isocyanate and N,N-dimethylformamide in a mass ratio of 1:1, and the protective liquid is prepared by N,N-dimethylformamide and methanol in a dosage ratio of 10mL:1mL. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and distilled under reduced pressure until no liquid is produced to obtain modified polyacrylate.
[0033] Furthermore, the preparation method of the flame retardant curing agent comprises the following steps:
[0034] B1. Add 2,4-dichloro-6-phenyl-1,3,5-triazine, 1,5-hexadiene-3,4-diol, saturated sodium hydroxide solution and dimethyl sulfoxide into a reaction kettle, raise the temperature of the reaction kettle to 40-50° C., keep the temperature for reaction for 2-4 hours, and perform post-treatment to obtain a triazine derivative;
[0035] B2, adding a triazine derivative, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum chloride and dimethyl sulfoxide into a reaction kettle, raising the temperature of the reaction kettle to 40-50° C., keeping the temperature for reaction for 1-3 hours, and post-treating to obtain a phosphorous triazine;
[0036] B3. Add phosphotriazine and benzoic acid peroxide into a reaction kettle and stir. Raise the temperature of the reaction kettle to 40-50°C, keep the temperature for 20-30 minutes, and perform post-processing to obtain a flame retardant curing agent.
[0037] The reaction equation for preparing the flame retardant curing agent is:
[0038]
[0039] Where:
[0040] The reaction principle for preparing the flame retardant curing agent is as follows: under alkaline and heating conditions, the halogen group on 2,4-dichloro-6-phenyl-1,3,5-triazine reacts with the hydroxyl group on 1,5-hexadiene-3,4-diol to form a long-chain structure through continuous polymerization, and the flame-retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is cross-linked on the long-chain structure through phosphine-hydrogen addition, and finally the residual double bonds on the chain segments are oxidized into epoxy groups through oxidation with benzoic acid peroxide.
[0041] Further, in step B1, the amount ratio of 2,4-dichloro-6-phenyl-1,3,5-triazine, 1,5-hexadiene-3,4-diol, saturated sodium hydroxide solution and dimethyl sulfoxide is 8-10g:5-6g:2-3mL:30-40mL, and the post-treatment includes: after the reaction is completed, the temperature of the reaction kettle is lowered to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 120-150°C, and the triazine derivative is obtained by distillation under reduced pressure until no liquid is extracted; in step B2, the amount ratio of the triazine derivative, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum chloride and dimethyl sulfoxide is 8-10 g:2-3g:0.5-0.8g:30-40mL, post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 120-150°C, and the reaction mixture is distilled under reduced pressure until no liquid is produced to obtain phosphated triazine; in step B3, the stirring rate of the reactor is 80-120rpm, and the amount ratio of phosphated triazine to peroxybenzoic acid is 8-10g:0.3-0.5g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction mixture is distilled under reduced pressure until no liquid is produced to obtain a flame retardant curing agent.
[0042] The present invention also provides a flame retardant, wear-resistant, low-smoke, halogen-free material, which is obtained by using the preparation method of the flame retardant, wear-resistant, low-smoke, halogen-free material.
[0043] The present invention has the following beneficial effects:
[0044] 1. The present invention prepares flame-retardant capsules and cross-links them with modified polyacrylate segments to form a support, thereby significantly enhancing the wear resistance of the material. The flame-retardant curing agent and the polyacrylate segments are further cross-linked to form a complex spatial network structure. The two cooperate with each other to significantly improve the wear resistance of the material. During the combustion process, the aluminum hydroxide component of the shell layer of the flame-retardant capsule releases moisture and the internal reaction monomers are polymerized to form a silicon-oxygen structure under the promotion of the high-temperature initiator barium peroxide, which cooperates with the flame-retardant layer formed after the aluminum hydroxide is dehydrated to significantly enhance the flame retardant properties of the material. The flame-retardant structure in the flame-retardant curing agent decomposes and releases acidic substances to promote the carbonization of the triazine ring to form a molten carbon layer. The five-membered ring structure formed by cross-linking decomposes and releases flame-retardant gas, which promotes the foaming of the carbon layer, flame retardant and reduces smoke density. The purpose of enhancing the flame retardant properties of the material is achieved through the coordination between the materials.
[0045] 2. The flame-retardant capsule prepared by the present invention is composed of an aluminum hydroxide shell modified by a silane coupling agent and a silicon-based reactive monomer and an initiator. When the material is structurally damaged at room temperature, the aluminum hydroxide shell is broken to release the reactive monomer and the initiator. Under the catalysis of ultraviolet rays, the polyacrylate segments and the reactive monomers form free radicals under the action of the initiator. The polymerization between the organic segments and the monomers and the self-polymerization reaction between the monomers repair the structural damage. At the high temperature of combustion, the shell can also be decomposed to release water to form a pore structure to release the reactive monomer and the initiator. The self-polymerization at high temperature and the aluminum oxide structure formed after the shell is dehydrated cooperate with each other, which significantly enhances the flame retardant properties of the material. At the same time, the surface of the flame-retardant capsule has a large number of double bond structures, which hybridize the organic segments during the polymerization process with the organic segments and are uniformly dispersed inside the organic material, so that the wear resistance of the material is significantly improved.
[0046] 3. The present invention prepares a flame retardant curing agent with a large number of flame retardant groups and triazine rings cross-linked internally, and through the selection of monomers, a modified polyacrylate containing a large number of tertiary amine groups and nitrile groups in the chain segment is prepared, and the highly active isocyanate group is protected by methanol. When the two are cross-linked, the methanol on the polyacrylate is removed to reduce the isocyanate group, which reacts with the epoxy group on the flame retardant curing agent to form a five-membered ring structure, which significantly enhances the wear resistance of the material. In the process of combustion, the tertiary amine group and triazine ring in the organic chain segment are easy to carbonize and the nitrile group is easy to decompose and release flame retardant gas. The isocyanate group forms a five-membered ring structure with the flame retardant chain extender. The structure breaks under the high temperature of combustion to release flame retardant carbon dioxide and ammonia, which promotes the foaming of the molten carbon layer formed after carbonization to form a rich void structure, thereby cooperating with the flame retardant gas to block heat diffusion, and finally significantly improve the flame retardant performance of the material. DETAILED DESCRIPTION
[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The polyacrylic acid resin used in the present invention was purchased from Shanghai Yuanye Biotechnology Co., Ltd., with the product number S51652-500ml;
[0049] The structural formula of the diisopropyltin methoxy compound used in the present invention is Pr2Sn(OMe)2.
[0050] Example 1
[0051] This embodiment provides a method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material, comprising the following steps:
[0052] S1. Preparation of flame retardant capsules
[0053] Weigh: 8.0 g 3-(methacryloyloxy)propyltrimethoxysilane, 12.0 g tetramethyltetravinylcyclotetrasiloxane, 0.8 g barium peroxide, 0.6 g benzophenone and 42.0 mL aluminum isopropanol, add into the reaction kettle and stir for 5 minutes to obtain modified oil;
[0054] Weigh: 3.2 g polyvinyl alcohol and 64.0 mL deionized water to prepare a modified solution;
[0055] Weigh: 5.4 g of the modified oil phase solution was added to a high-speed homogenizer, and 24.0 mL of the aqueous phase liquid was poured into the modified oil liquid. The speed of the high-speed homogenizer was set to 8000 rpm, and stirred at room temperature for 20 min to obtain a modified emulsion;
[0056] Weigh: 40.0 mL of the modified latex was added to the reactor and stirred, 1.2 mol / L hydrochloric acid solution was added to the reactor to adjust the system pH to 5, the temperature of the reactor was raised to 40°C, and the reaction was kept warm for 3 hours. Then, 2.4 mL of aluminum isopropanol was added to the reactor, and the reaction was kept warm for 3 hours. Then, 3.6 mL of aluminum isopropanol was added to the reactor and the reaction was kept warm for 8 hours. After the reaction was completed, the temperature of the reaction liquid was lowered to room temperature, and the mixed liquid was centrifuged using a centrifuge. The speed of the centrifuge was controlled to 3000 rpm. After centrifugation for 10 minutes, the precipitate was collected, and after washing with anhydrous ethanol and deionized water for 3 times, the precipitate was placed in a drying oven at a temperature of 60°C and vacuum dried until the precipitate had a constant weight to obtain a self-repairing capsule;
[0057] Weigh: 16.0g self-repairing capsules, 5.4g vinyltriethoxysilane, 1.6g sodium hydroxide and 64.0mL deionized water are added to the reactor, the temperature of the reactor is raised to 30°C, and the heat treatment is carried out for 3h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a flame retardant capsule.
[0058] S2. Preparation of flame retardant curing agent
[0059] Weigh: 16.0 g 2,4-dichloro-6-phenyl-1,3,5-triazine, 12.0 g 1,5-hexadiene-3,4-diol, 5.4 mL saturated sodium hydroxide solution and 64.0 mL dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 40°C, and keep the temperature for 2 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 120°C, and distill under reduced pressure until no liquid is produced to obtain a triazine derivative;
[0060] Weigh: 16.0 g of a triazine derivative, 5.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 1.2 g of aluminum chloride and 64.0 mL of dimethyl sulfoxide are added to a reactor, the temperature of the reactor is raised to 40° C., and the reaction is kept warm for 1 hour. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 120° C., and distilled under reduced pressure until no liquid is produced to obtain phosphated triazine;
[0061] Weigh: 18.0g of phosphotriazine and 0.8g of benzoic acid peroxide are added to a reactor and stirred at a stirring rate of 80rpm. The temperature of the reactor is raised to 40°C and kept warm for 20min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is extracted to obtain a flame retardant curing agent.
[0062] S3. Preparation of flame retardant polyurethane
[0063] Weigh: 10.0 g of methacryloyl isocyanate and 10.0 g of N,N-dimethylformamide to prepare a methacryloyl isocyanate solution;
[0064] Weigh: 100.0 mL N,N-dimethylformamide and 10.0 mL methanol to prepare a protective solution;
[0065] Weigh: 12.0g of dimethylaminoethyl acrylate, 16.0g of 1,2-isopropylidene glycerol 2-cyanoacrylate, 3.2g of azobisisobutyronitrile and 120.0mL of N,N-dimethylformamide, add them to a reactor and stir, introduce nitrogen protection, then drop 40.0mL of methacryloyl isocyanate solution into the reactor, raise the temperature of the reactor to 70°C, keep the reaction for 2h, then lower the temperature of the reactor to 40°C, continue to drop 24.0mL of protective solution into the reactor, keep the reaction for 20min, after the reaction is completed, wait for the temperature of the reactor to drop to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain modified polyacrylate;
[0066] Weigh: 16.0g modified polyacrylate and 64.0mL dimethyl sulfoxide are added to the reactor, the temperature of the reactor is raised to 150°C, and after stirring for 15 minutes, 1.6g azobisisobutyronitrile and 5.4g flame retardant capsules are added to the reactor, and the reaction is kept warm for 20 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 120°C, and reduced pressure distillation is carried out until no liquid is produced to obtain flame retardant polyacrylate.
[0067] S4. Preparation of flame retardant and wear resistant materials
[0068] Weigh: 18.0g flame retardant polyacrylate, 8.4g diisopropyltin methoxy compound and 64.0mL dimethyl sulfoxide are added to the reactor, after nitrogen protection is introduced, the temperature of the reactor is raised to 70°C, and the reaction is kept warm for 20 minutes, and 4.0g flame retardant curing agent is added to the reactor, and the reaction is kept warm for 1 hour. After the reaction is completed by post-treatment, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 120°C, and the vacuum distillation is carried out until no liquid is produced to obtain a solidified polyacrylate;
[0069] Weigh: 88.0g of cured polyacrylate, 12.4g of flame retardant capsules, 18.0g of dioctyl phthalate, 8.4g of butylated hydroxytoluene, 3.6g of calcium stearate and 3.6g of tri-tert-butyl hydroxyphenyl acrylate and add them into a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 170°C, 185, 185°C, 200°C, 200°C, 210°C, and 210°C, respectively. The main engine speed of the twin-screw extruder is 100rpm, the pressure is 80bar, and the flame-retardant and wear-resistant material is obtained by melt extrusion.
[0070] Example 2
[0071] This embodiment provides a method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material, comprising the following steps:
[0072] S1. Preparation of flame retardant capsules
[0073] Weigh: 8.4 g 3-(methacryloyloxy)propyltrimethoxysilane, 12.0 g tetramethyltetravinylcyclotetrasiloxane, 0.8 g barium peroxide, 0.8 g benzophenone and 42.0 mL aluminum isopropanol, add into the reaction kettle and stir for 5 minutes to obtain modified oil;
[0074] Weigh: 1.6 g polyvinyl alcohol and 36.0 mL deionized water to prepare a modified solution;
[0075] Weigh: 6.0 g of the modified oil phase solution was added to a high-speed homogenizer, and 24.0 mL of the aqueous phase liquid was poured into the modified oil liquid. The speed of the high-speed homogenizer was set to 9000 rpm, and stirred at room temperature for 30 min to obtain a modified emulsion;
[0076] Weigh: 40.0mL of modified latex was added to the reactor and stirred, 2.0mol / L hydrochloric acid solution was added to the reactor to adjust the system pH to 4, the temperature of the reactor was raised to 40°C, and the reaction was kept warm for 3 hours. Then, 2.4mL of aluminum isopropanol was added to the reactor, and the reaction was kept warm for 3 hours. Then, 3.6mL of aluminum isopropanol was added to the reactor and the reaction was kept warm for 12 hours. After the reaction was completed, the temperature of the reaction liquid was lowered to room temperature, and the mixed liquid was centrifuged using a centrifuge. The speed of the centrifuge was controlled to 5000rpm. After centrifugation for 15 minutes, the precipitate was collected, and after washing with anhydrous ethanol and deionized water for 5 times, the precipitate was placed in a drying oven at a temperature of 60°C and vacuum dried until the precipitate had a constant weight to obtain a self-repairing capsule;
[0077] Weigh: 18.0g self-repairing capsules, 6.0g vinyltriethoxysilane, 1.6g sodium hydroxide and 64.0mL deionized water and add them into the reactor. The temperature of the reactor is raised to 50°C and kept warm for 5h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at 60°C and vacuum dried until the filter cake has constant weight to obtain a flame retardant capsule.
[0078] S2. Preparation of flame retardant curing agent
[0079] Weigh: 18.0 g 2,4-dichloro-6-phenyl-1,3,5-triazine, 10.8 g 1,5-hexadiene-3,4-diol, 5.4 mL saturated sodium hydroxide solution and 64.0 mL dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 50° C., and keep the reaction for 4 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 150° C., and distill under reduced pressure until no liquid is produced to obtain a triazine derivative;
[0080] Weigh: 20.0 g of a triazine derivative, 6.0 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 1.2 g of aluminum chloride and 72.0 mL of dimethyl sulfoxide, add them into a reactor, raise the temperature of the reactor to 50° C., and keep the temperature for 3 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 150° C., and distill under reduced pressure until no liquid is produced to obtain phosphated triazine;
[0081] Weigh: 18.0g of phosphotriazine and 0.8g of benzoic acid peroxide are added to a reactor and stirred at a stirring rate of 120rpm. The temperature of the reactor is raised to 50°C and kept warm for 30min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is extracted to obtain a flame retardant curing agent.
[0082] S3. Preparation of flame retardant polyurethane
[0083] Weigh: 10.0 g of methacryloyl isocyanate and 10.0 g of N,N-dimethylformamide to prepare a methacryloyl isocyanate solution;
[0084] Weigh: 100.0 mL N,N-dimethylformamide and 10.0 mL methanol to prepare a protective solution;
[0085] Weigh: 16.0g of dimethylaminoethyl acrylate, 20.0g of 1,2-isopropylidene glycerol 2-cyanoacrylate, 3.6g of azobisisobutyronitrile and 150.0mL of N,N-dimethylformamide, add them into a reactor and stir, after nitrogen protection, add 60.0mL of methacryloyl isocyanate solution dropwise into the reactor, raise the temperature of the reactor to 80°C, keep the reaction for 4h, then reduce the temperature of the reactor to 50°C, continue to add 36.0mL of protective solution dropwise into the reactor, keep the reaction for 40min, after the reaction is completed, wait for the temperature of the reactor to be reduced to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain modified polyacrylate;
[0086] Weigh: 16.0g modified polyacrylate and 64.0mL dimethyl sulfoxide are added to the reactor, the temperature of the reactor is raised to 155°C, and after stirring for 20 minutes, 1.8g azobisisobutyronitrile and 5.4g flame retardant capsules are added to the reactor, and the reaction is kept warm for 30 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 150°C, and reduced pressure distillation is performed until no liquid is produced to obtain flame retardant polyacrylate.
[0087] S4. Preparation of flame retardant and wear resistant materials
[0088] Weigh: 18.0g flame retardant polyacrylate, 8.4g diisopropyltin methoxy compound and 64.0mL dimethyl sulfoxide are added to the reactor, after nitrogen protection, the temperature of the reactor is raised to 80°C, and the reaction is kept warm for 30 minutes, and 5.4g flame retardant curing agent is added to the reactor, and the reaction is kept warm for 2 hours. After the reaction is completed by post-treatment, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 150°C, and the vacuum distillation is carried out until no liquid is produced to obtain a solidified polyacrylate;
[0089] Weigh: 96.0g of cured polyacrylate, 14.4g of flame retardant capsules, 24.0g of dioctyl phthalate, 4.8g of butylated hydroxytoluene, 4.8g of calcium stearate and 3.6g of tri-tert-butyl hydroxyphenyl acrylate and add them into a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 170°C, 185, 185°C, 200°C, 200°C, 210°C, and 210°C, respectively. The main engine speed of the twin-screw extruder is 120rpm, the pressure is 120bar, and the flame-retardant and wear-resistant material is obtained by melt extrusion.
[0090] Example 3
[0091] This embodiment provides a method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material, comprising the following steps:
[0092] S1. Preparation of flame retardant capsules
[0093] Weigh: 9.6 g 3-(methacryloyloxy)propyltrimethoxysilane, 14.8 g tetramethyltetravinylcyclotetrasiloxane, 0.8 g barium peroxide, 0.8 g benzophenone and 48.0 mL aluminum isopropanol, add into the reaction kettle and stir for 8 minutes to obtain modified oil;
[0094] Weigh: 2.0 g polyvinyl alcohol and 40.0 mL deionized water to prepare a modified solution;
[0095] Weigh: 5.4 g of the modified oil phase solution was added to a high-speed homogenizer, and 24.0 mL of the aqueous phase liquid was poured into the modified oil liquid. The speed of the high-speed homogenizer was set to 9000 rpm, and stirred at room temperature for 24 min to obtain a modified emulsion;
[0096] Weigh: 40.0 mL of the modified latex was added to the reactor and stirred, 1.5 mol / L hydrochloric acid solution was added to the reactor to adjust the system pH to 4, the reactor temperature was raised to 45°C, and after the reaction was kept warm for 3 hours, 2.4 mL of aluminum isopropanol was added to the reactor, and the reaction was kept warm for 3 hours. Then, 3.6 mL of aluminum isopropanol was added to the reactor and the reaction was kept warm for 10 hours. After the reaction was completed, the temperature of the reaction liquid was lowered to room temperature, and the mixed solution was centrifuged using a centrifuge. The speed of the centrifuge was controlled to 4000 rpm. After centrifugation for 12 minutes, the precipitate was collected, and after washing with anhydrous ethanol and deionized water for 4 times, the precipitate was placed in a drying oven at a temperature of 60°C and vacuum dried until the precipitate had a constant weight to obtain a self-repairing capsule;
[0097] Weigh: 18.0g self-repairing capsules, 5.4g vinyltriethoxysilane, 1.8g sodium hydroxide and 84.0mL deionized water are added into the reactor, the temperature of the reactor is raised to 40°C, and the temperature is kept for 4h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a flame retardant capsule.
[0098] S2. Preparation of flame retardant curing agent
[0099] Weigh: 18.0 g 2,4-dichloro-6-phenyl-1,3,5-triazine, 10.8 g 1,5-hexadiene-3,4-diol, 5.4 mL saturated sodium hydroxide solution and 72.0 mL dimethyl sulfoxide, add into a reactor, raise the temperature of the reactor to 45°C, keep warm for 3 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 135°C, and distill under reduced pressure until no liquid is produced to obtain a triazine derivative;
[0100] Weigh: 18.0 g of a triazine derivative, 5.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 1.6 g of aluminum chloride and 72.0 mL of dimethyl sulfoxide are added to a reactor, the reactor temperature is raised to 45° C., and the reaction is kept warm for 2 hours. After the reaction is completed, the reactor temperature is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 135° C., and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain phosphated triazine;
[0101] Weigh: 18.0g of phosphotriazine and 0.8g of benzoic acid peroxide are added to a reactor and stirred at a stirring rate of 100rpm. The temperature of the reactor is raised to 45°C and kept warm for 25min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is extracted to obtain a flame retardant curing agent.
[0102] S3. Preparation of flame retardant polyurethane
[0103] Weigh: 10.0 g of methacryloyl isocyanate and 10.0 g of N,N-dimethylformamide to prepare a methacryloyl isocyanate solution;
[0104] Weigh: 100.0 mL N,N-dimethylformamide and 10.0 mL methanol to prepare a protective solution;
[0105] Weigh: 14.8g of dimethylaminoethyl acrylate, 18.0g of 1,2-isopropylidene glycerol 2-cyanoacrylate, 3.6g of azobisisobutyronitrile and 150.0mL of N,N-dimethylformamide, add them to a reactor and stir, introduce nitrogen protection, then drop 48.0mL of methacryloyl isocyanate solution into the reactor, raise the temperature of the reactor to 75°C, keep the reaction for 3h, then lower the temperature of the reactor to 45°C, continue to drop 32.0mL of protective solution into the reactor, keep the reaction for 30min, after the reaction is completed, wait for the temperature of the reactor to drop to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain modified polyacrylate;
[0106] Weigh: 18.0g modified polyacrylate and 72.0mL dimethyl sulfoxide are added to the reactor, the temperature of the reactor is raised to 155°C, and after stirring for 18 minutes, 1.8g azobisisobutyronitrile and 5.4g flame retardant capsules are added to the reactor, and the reaction is kept warm for 24 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 135°C, and reduced pressure distillation is carried out until no liquid is produced to obtain flame retardant polyacrylate.
[0107] S4. Preparation of flame retardant and wear resistant materials
[0108] Weigh: 18.0g flame retardant polyacrylate, 8.4g diisopropyltin methoxy compound and 72.0mL dimethyl sulfoxide are added to the reactor, and after nitrogen protection is introduced, the temperature of the reactor is raised to 72°C, and the reaction is kept warm for 24 minutes, and 5.4g flame retardant curing agent is added to the reactor, and the reaction is kept warm for 2 hours. After the reaction is completed by post-treatment, the temperature of the reactor is lowered to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 135°C, and the reaction is distilled under reduced pressure until no liquid is produced to obtain a solidified polyacrylate;
[0109] Weigh: 96.0g of cured polyacrylate, 12.0g of flame retardant capsules, 18.0g of dioctyl phthalate, 4.8g of butylated hydroxytoluene, 3.6g of calcium stearate and 3.6g of tri-tert-butyl hydroxyphenyl acrylate and add them into a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 170°C, 185, 185°C, 200°C, 200°C, 210°C, and 210°C, respectively. The main engine speed of the twin-screw extruder is 100rpm, the pressure is 100bar, and the flame-retardant and wear-resistant material is obtained by melt extrusion.
[0110] Comparative Example 1
[0111] The difference between this comparative example and Example 3 is that the step of preparing flame-retardant capsules is eliminated in step S1, the use of flame-retardant capsules is eliminated in the process of preparing flame-retardant polyurethane in step S3, and self-repairing capsules are used to replace flame-retardant capsules in equal amounts in the process of preparing flame-retardant and wear-resistant materials in step S4.
[0112] Comparative Example 2
[0113] The difference between this comparative example and Example 3 is that the step of preparing the flame retardant curing agent in step S2 is eliminated, and in the process of preparing the cured polyacrylate in step S4, an equal amount of triazine derivatives is used to replace the flame retardant curing agent.
[0114] Comparative Example 3
[0115] The difference between this comparative example and Example 3 is that the step of preparing flame-retardant polyacrylic acid in step S3 is eliminated, and in the process of preparing flame-retardant polyacrylate in step S4, an equal amount of modified polyacrylate is used to replace flame-retardant polyacrylate.
[0116] Performance Test:
[0117] The vertical combustion grade of the flame retardant and wear-resistant materials prepared in Examples 1-3 and Comparative Examples 1-3 was determined with reference to the standard GB / T 2408-2021 “Horizontal and vertical methods for determination of combustion performance of plastics”;
[0118] The limiting oxygen index of the flame retardant and wear resistant materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test";
[0119] The volume wear of the flame retardant and wear resistant materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method)";
[0120] The tensile strength, smoke density and acidity of combustion released gas of the flame retardant and wear-resistant materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 32129-2015 "Halogen-free low-smoke flame retardant cable materials for wires and cables";
[0121] The self-repairing time of the flame-retardant and wear-resistant materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard HG / T 5675-2020 "Self-repairing hardened film of optical functional film". The specific data are shown in Table 1.
[0122] Table 1
[0123]
[0124]
[0125] Data Analysis:
[0126] By comparing and analyzing the data in Table 1 above, the vertical combustion grade of the polyurethane material prepared by the present invention is V-0, and the volume wear amount is 30.5 mm 3 , tensile strength is 60.6MPa, flame smoke density is 115, flameless smoke density is 49, combustion gas acidity (HCl and HBr content / %) is 0.01% and self-repair time is 7min;
[0127] By comparing the data of Example 3 and Comparative Example 1, it can be found that the volume wear of the flame-retardant and wear-resistant material is significantly increased, and the tensile strength and self-repairing performance are significantly reduced, indicating that the flame-retardant capsules modified with a large number of double bonds on the surface form stable crosslinks through double bonds and polyacrylic acid segments, so that the flame-retardant capsules are fully and evenly dispersed inside the polymer segments, significantly enhancing the wear resistance, tensile strength and self-repairing performance of the material;
[0128] By comparing the data of Example 3 and Comparative Example 2, it can be found that the flame retardant properties of the flame retardant and wear-resistant material are significantly reduced, indicating that a large number of flame retardant groups are modified on the flame retardant curing agent prepared by the present invention, which decomposes at high temperatures, promotes the carbonization and gas volatilization of the material, and ultimately significantly improves the flame retardant properties of the material, and its chain segments have a large number of triazine ring structures that are easy to carbonize to form carbon structures. After carbonization, a molten carbon layer is formed, and a porous structure is formed after gas foaming, which significantly enhances the flame retardant properties of the material.
[0129] By comparing the data of Example 3 and Comparative Example 3, it can be found that the flame retardant properties of the flame retardant and wear-resistant material are significantly reduced, indicating that the modified polyacrylate prepared by the present invention contains a large number of tertiary amine groups and nitrile groups. During the combustion process, the tertiary amine groups are easily carbonized and the nitrile groups are easily decomposed to release flame retardant gases. The polyacrylate has a protected isocyanate group, and the isocyanate group has a five-membered oxazolidinone ring structure on the flame retardant chain extender. The structure breaks under high temperature of combustion to release flame retardant carbon dioxide and ammonia, which significantly enhances the flame retardant properties of the material.
[0130] It is explained that the present invention significantly enhances the wear resistance of the material by preparing flame-retardant capsules and cross-linking with modified polyacrylate segments to form a support, and further cross-linking with the polyacrylate segments through the flame-retardant curing agent to form a complex spatial network structure, and the synergistic cooperation of the two significantly improves the wear resistance of the material; during the combustion process, the aluminum hydroxide component of the shell layer of the flame-retardant capsule releases moisture and the internal reaction monomers are polymerized to form a silicon-oxygen structure under the promotion of the high-temperature initiator barium peroxide, and the synergistic cooperation with the flame-retardant layer formed after dehydration of aluminum hydroxide significantly enhances the flame retardant properties of the material, and the flame-retardant structure in the flame-retardant curing agent decomposes to release acidic substances to promote the carbonization of the triazine ring to form a molten carbon layer, and the five-membered ring structure formed by cross-linking decomposes to release flame-retardant gas, promotes the foaming of the carbon layer, flame retardant and reduces smoke density, and the purpose of enhancing the flame retardant properties of the material is achieved through the coordination between materials.
[0131] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material, characterized in that: The following steps are involved: S1. Add self-repairing capsules, vinyl triethoxysilane, sodium hydroxide and deionized water into a reactor, raise the temperature of the reactor to 30-50°C, keep the temperature for 3-5h, and post-treat to obtain flame-retardant capsules; S2, adding modified polyacrylate and dimethyl sulfoxide into a reactor, raising the temperature of the reactor to 150-160°C, stirring for 15-20 minutes, adding azobisisobutyronitrile and flame retardant capsules into the reactor, and reacting for 20-30 minutes to obtain flame retardant polyacrylate; S3, adding flame retardant polyacrylate, diisopropyltin methoxy compound and dimethyl sulfoxide into a reactor, introducing nitrogen protection, raising the temperature of the reactor to 70-80°C, keeping the temperature for reaction for 20-30 minutes, adding a flame retardant curing agent into the reactor, keeping the temperature for reaction for 1-2 hours, and post-treating to obtain cured polyacrylate; S4, adding the solidified polyacrylate, the flame retardant capsule and the auxiliary materials into a twin-screw extruder for melt extrusion to obtain a flame retardant and wear resistant material.
2. The method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material according to claim 1, characterized in that: In step S1, the amount ratio of self-repairing capsules, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water is 8-10g:2-3g:0.8-1g:30-50mL; in step S2, the amount ratio of modified polyacrylate, dimethyl sulfoxide, azobisisobutyronitrile and flame retardant capsules is 8-10g:30-40mL:0.8-1g:2-3g; in step S3, the amount ratio of flame retardant polyacrylate, diisopropyltin methoxy compound, dimethyl sulfoxide and flame retardant curing agent is 8-10g:3-5g:30-40mL:2-3g; in step S4, the amount ratio of cured polyacrylate, flame retardant capsules and auxiliary materials is 80-100g:10-15g:30-40g.
3. The method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material according to claim 1, characterized in that: The preparation method of the self-repairing capsule comprises the following steps: A1. Add 3-(methacryloyloxy)propyltrimethoxysilane, tetramethyltetravinylcyclotetrasiloxane, barium peroxide, benzophenone and aluminum isopropanol into a reaction kettle and stir for 5-10 minutes to obtain a modified oil; A2, adding the modified oil phase solution into a high-speed homogenizer, and pouring the aqueous phase into the modified oil liquid, setting the speed of the high-speed homogenizer to 8000-9000rpm, stirring at room temperature for 20-30min, to obtain a modified emulsion; A3. Add the modified emulsion into the reactor and stir. Add 1-2 mol / L hydrochloric acid solution into the reactor to adjust the pH value of the system to 4-5. Raise the temperature of the reactor to 40-50°C. After keeping the temperature for 3-4 hours, add aluminum isopropanol into the reactor. After keeping the temperature for 3-4 hours, add aluminum isopropanol again. Keep the temperature for 8-12 hours. After post-treatment, obtain the self-repairing capsule.
4. The method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material according to claim 1, characterized in that: The preparation method of the modified polyacrylate comprises the following steps: adding dimethylaminoethyl acrylate, 1,2-isopropylidene glycerol 2-cyanoacrylate, azobisisobutyronitrile and N,N-dimethylformamide into a reaction kettle and stirring, introducing nitrogen for protection, dripping methacryloyl isocyanate solution into the reaction kettle, raising the temperature of the reaction kettle to 70-80°C, keeping the temperature for reaction for 2-4h, lowering the temperature of the reaction kettle to 40-50°C, continuing to drip protective solution into the reaction kettle, keeping the temperature for reaction for 20-40min, and performing post-treatment to obtain the modified polyacrylate.
5. The method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material according to claim 4, characterized in that: The dosage ratio of dimethylaminoethyl acrylate, 1,2-isopropylidene glycerol 2-cyanoacrylate, azobisisobutyronitrile, N,N-dimethylformamide, methacryloyl isocyanate solution and protective liquid is 6-8g:8-10g:1-2g:60-80mL:20-30mL:10-20mL, the methacryloyl isocyanate solution is prepared by methacryloyl isocyanate and N,N-dimethylformamide in a mass ratio of 1:1, and the protective liquid is prepared by N,N-dimethylformamide and methanol in a dosage ratio of 10mL:1mL.
6. The method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material according to claim 1, characterized in that: The preparation method of the flame retardant curing agent comprises the following steps: B1. Add 2,4-dichloro-6-phenyl-1,3,5-triazine, 1,5-hexadiene-3,4-diol, saturated sodium hydroxide solution and dimethyl sulfoxide into a reaction kettle, raise the temperature of the reaction kettle to 40-50° C., keep the temperature for reaction for 2-4 hours, and perform post-treatment to obtain a triazine derivative; B2, adding a triazine derivative, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum chloride and dimethyl sulfoxide into a reaction kettle, raising the temperature of the reaction kettle to 40-50° C., keeping the temperature for reaction for 1-3 hours, and post-treating to obtain a phosphorous triazine; B3. Add phosphotriazine and benzoic acid peroxide into a reaction kettle and stir. Raise the temperature of the reaction kettle to 40-50°C, keep the temperature for 20-30 minutes, and perform post-processing to obtain a flame retardant curing agent.
7. The method for preparing a flame retardant, wear-resistant, low-smoke, halogen-free material according to claim 6, characterized in that: In step B1, the amount ratio of 2,4-dichloro-6-phenyl-1,3,5-triazine, 1,5-hexadiene-3,4-diol, saturated sodium hydroxide solution and dimethyl sulfoxide is 8-10g:5-6g:2-3mL:30-40mL; in step B2, the amount ratio of triazine derivative, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum chloride and dimethyl sulfoxide is 8-10g:2-3g:0.5-0.8g:30-40mL; in step B3, the stirring rate of the reactor is 80-120rpm, and the amount ratio of phosphated triazine and benzoic acid peroxide is 8-10g:0.3-0.5g.
8. A flame retardant, wear-resistant, low-smoke, halogen-free material, characterized in that: The flame-retardant, wear-resistant, low-smoke, halogen-free material is obtained by processing using the method for preparing a flame-retardant, wear-resistant, low-smoke, halogen-free material as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Flame-retardant low-smoke anti-abrasive PVC floor and preparing method thereof
CN110066478A
Phase change microcapsule and preparation method thereof
CN112295516A
Preparation method and application of organic silicon modified acrylate bedplate glue
CN112662345A
Self-repairing optical cable and preparation method thereof
CN112812438A
Wear-resistant flame-retardant resin composition, molded article, and wear-resistant insulated wire
JP2012082277A
Cited By
Flame-retardant aging-resistant cable for solar power generation and preparation method thereof
CN120137409A